The Ten-Step Vaginal Hysterectomy A Newer and Better Approach - Bina, I; Akhter, D (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Aims and Objectives: This study was undertaken to compare with the traditional Heaneys method of vaginal hysterectomy and the newer Ten-Step Vaginal Hysterectomy and to emphasize that this is a safe procedure with lesser blood loss, shorter operation time and shorter requirements of analgesia. Study Design: 110 Patients with non descent, first, second and third degree prolapsed uterus from 45 to 72 years of age were subjected to this study in Khalishpur Clinic. Those women were randomly selected. Among them 54 women had the traditional Heanys Methods of Vaginal Hysterectomy and 56 women had the Ten-Step Vaginal Hysterectomy (TSVH). The blood loss was measured by hemoglobin assessment before and 3 days after operation. Material and Methods: In Ten-Step Vaginal Hysterectomy the vaginal wall was incised by drop-like incision starting under the urethra, continuing laterally and down, encircling the cervix from behind and returning back to the starting point from the other side, then separation was done laterally to the side to the uterus. Bladder is detached from the uterus, and the posterior peritoneum is opened. The sacro-uterine ligaments and the paracervical ligaments are clamped together, cut and ligated in both sides. Next the uterine arteries are clamped, cut and ligated. Uterus is pulled down and two fingers are introduced behind the fundus to lift anterior peritoneum and opened under supervision. The round and ovarian ligaments and blood vessels are clamped together and ligated in both side. The peritoneum is left open, then reconstruction of the pelvic floor is done and the vaginal wall is closed continuously. Results: It was found that in comparison of traditional methods with the ten steps vaginal hysterectomy, there are lesser blood loss (400ml vs 80ml; P<0.05) with lower complications, shorter operation time (52.5min vs 30.3min; P<0.05), lesser pain and lesser requirements of analgesia (5.8 vs 3.9 days; P<0.05) and shorter period of convalescence. Hospital stay remains same for both groups. Conclusion: The Ten-Step Vaginal Hysterectomy is a better operation than traditional method of vaginal hysterectomy, Abdominal Hysterectomy and LAVH. At the same time this method is logical and easy to learn, to perform and to teach. DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11407 J Bangladesh Coll Phys Surg 2012; 30: 71-77